2006
DOI: 10.2514/1.15597
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic Loads on Airfoil with Trailing-Edge Flap Pitching with Different Frequencies

Abstract: Unsteady aerodynamic loads on NACA 0012 airfoil with a trailing-edge flap were measured in wind tunnel and calculated from a simple theoretical model. The airfoil model of 0.18 m chord length used in wind-tunnel test was oscillating in pitch about an axis located at 35% chord length from the airfoil leading edge. The length of trailingedge flap was 22.6% of airfoil chord. The flap was also deflecting harmonically, but with frequency different from airfoil pitching motion. The influence of phase delay between a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…Differently for steady simulations the solver output loads are directly used in eqn. (22), which as a consequence has no imaginary terms. On the other hand, C LK (p) and C mK (p) are the KS aerodynamic loads to be computed by the optimization algorithm according to the free parameters in p. The array p contains the geometrical and motion free parameters of the KS model discussed in the above, see also figure 5.…”
Section: Reduced Order Model For a Rotor Blade Section Equipped mentioning
confidence: 96%
See 1 more Smart Citation
“…Differently for steady simulations the solver output loads are directly used in eqn. (22), which as a consequence has no imaginary terms. On the other hand, C LK (p) and C mK (p) are the KS aerodynamic loads to be computed by the optimization algorithm according to the free parameters in p. The array p contains the geometrical and motion free parameters of the KS model discussed in the above, see also figure 5.…”
Section: Reduced Order Model For a Rotor Blade Section Equipped mentioning
confidence: 96%
“…According to equation (22) the optimization procedure is performed with respect to a set p of free parameters affecting KS loads. In the present case of oscillating L-tab with airfoil in fixed position, the array p reads:…”
Section: Via Numerical Simulations For Steady Airfoil With Harmonicmentioning
confidence: 99%
“…30. The experiments were conducted for a pitching NACA0012 airfoil with a trailing edge flap oscillating simultaneously at different frequencies.…”
Section: Comparison With Available Experimental Datamentioning
confidence: 99%
“…[14], and suggested that the morphing motion has an influence on the flow field Nevertheless, the use of morphing flaps as an active flow control has not thoroughly been explored as opposed to the use of oscillating, discreet hinged flaps for instance. Krzysiak et al [18] investigated a pitching NACA 0012 airfoil with a harmonically deflecting TEF in a subsonic wind tunnel and compared the results with theoretical calculations. It was found that an increase in the maximum lift coefficient is possible when both the angle of attack of the airfoil and flap deflection increase simultaneously.…”
Section: Introductionmentioning
confidence: 99%